Three types of preS1 start codon deletion variants in the natural course of chronic hepatitis B infection. Issue 7 (27th February 2018) - Choe, Won Hyeok; Kim, Hong; Lee, So‐Young; Choi, Yu‐Min; Kwon, So Young; Moon, Hee Won; Hur, Mina; Kim, Bum‐Joon
Abstract: Background and Aim: Naturally occurring hepatitis B virus variants carrying a deletion in the preS1 start codon region may evolve during long‐lasting virus–host interactions in chronic hepatitis B (CHB). The aim of this study was to determine the immune phase‐specific prevalent patterns of preS1 start codon deletion variants and related factors during the natural course of CHB. Methods: A total of 399 CHB patients were enrolled. Genotypic analysis of three different preS1 start codon deletion variants (classified by deletion size: 15‐base pair [bp], 18‐bp, and 21‐bp deletion variants) was performed. Results: PreS1 start codon deletion variants were detected in 155 of 399 patients (38.8%). The predominant variant was a 15‐bp deletion in the immune‐tolerance phase (18/50, 36%) and an 18‐bp deletion in the immune‐clearance phase (69/183, 37.7%). A 21‐bp deletion was the predominant variant in the low replicative phase (3/25, 12.0%) and reactivated hepatitis Be antigen (HBeAg)‐negative phase (22/141, 15.6%). The 15‐bp and 18‐bp deletion variants were more frequently found in HBeAg‐positive patients ( P  < 0.010 and P  < 0.001, respectively), whereas the 21‐bp deletion variant was more frequently found in HBeAg‐negative patients ( P  < 0.001). On multiple logistic regression analyses, the 21‐bp deletion variant was independently associated with liver cirrhosis ( P  = 0.006), and the 15‐bp deletion variant was significantly related to an incomplete response to antiviral agents ( P  = 0.012). Conclusions: The predominant type of preS1 start codon deletion variants changes according to the immune phases of CHB infection, and each variant type is associated with different clinical parameters. PreS1 start codon deletion variants might interact with the host immune response differently according to their variant types.